Louis Braille (1809-1852) – twórca pisma dla niewidomych - Maciejewicz, Piotr; Kopacz, Dorota (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
Louis Braille was born on January 4th 1809 in Coupvray, France. An injury to his eye at the age of three, resulted in total loss of vision. In 1819 he entered the Institute for Blind Youth in Paris. There he would live, study, and later teach. When he was fifteen, he developed system of reading and writing by means of raised dots, which is known today as Braille. The basis of the Braille system is known as a Braille cell. The cell is comprised of six dots numbered in a specific order. Each dot or combination of dots represents a letter of the alphabet. This Braille system has established itself internationally and formed the basic Braille for all languages.